2016
DOI: 10.1186/s12014-016-9104-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting LAMP2 in human cerebrospinal fluid with a combination of immunopurification and high resolution parallel reaction monitoring mass spectrometry

Abstract: Background: Alzheimer's disease is the most common form of dementia. An increasing body of evidence suggests that endo-lysosomal dysfunction is a pathogenic mechanism of Alzheimer's disease. Thus there is a potential for proteins involved in the normal function of endo-lysosomal vesicles to act as biomarkers of disease. Herein we focused on the lysosomal protein LAMP2 that is involved in chaperone mediated autophagy.Results: Using a combination of immunoprecipitation, digestion and nano-liquid chromatography t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 50 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…The levels of all three peptides were reported to increase in AD compared to controls. LAMP2 did not correlate with any of the AD core biomarkers [42]. [43].…”
Section: Targeted Quantification By Mass Spectrometrymentioning
confidence: 81%
See 1 more Smart Citation
“…The levels of all three peptides were reported to increase in AD compared to controls. LAMP2 did not correlate with any of the AD core biomarkers [42]. [43].…”
Section: Targeted Quantification By Mass Spectrometrymentioning
confidence: 81%
“…Hence, proteins involved in the normal function of endo-lysosomal vesicles could be tentative biomarkers of AD. The lysosomal protein LAMP2 is involved in chaperone mediated autophagy and recently it was shown that the concentrations of three CSF LAMP2 peptides were increased in AD compared to non-AD controls [42]. Altered CSF LAMP2 concentrations may indicate endo-lysosomal dysfunction in AD, but further studies of larger cohorts also including patients with other neurodegenerative disorders are required.…”
Section: Targeted Enrichment By Immunoprecipitationmass Spectrometrymentioning
confidence: 99%
“…The approach has been successfully implemented previously both by our laboratory and others . When attempting this approach with an abundance difference of 10 3 or higher the low intensity peak reproducibility was reduced (data not shown) and the standard approach with separate isolations should be used.…”
Section: Discussionmentioning
confidence: 99%
“…PRM offers highly accurate and selective measurements and can successfully be applied to the analysis of complex samples . With good precision, we have previously measured the lysosomal membrane protein LAMP2 in CSF using PRM . Furthermore, measurements using PRM have shown similar performance compared to SRM, however, with the advantage of a broader dynamic range …”
Section: Discussionmentioning
confidence: 99%